From Evidence to Understanding: A Precarious Path - Hand,DJ (European Review, 2013)
Falsifiability is the cornerstone of science. However, Rutherford notwithstanding, almost by definition science functions at the limits of measurement accuracy and theoretical grasp, so that statistical analysis is central to scientific advance. This applies as much to physics as it does to psychology, as much to geology as to biology. I look at some of the potholes in the path of scientific discovery, showing how easy it is to stumble, and at some of the consequences for the scientific endeavour.